2016
DOI: 10.1080/23294515.2016.1170075
|View full text |Cite
|
Sign up to set email alerts
|

Organizational values in the provision of access to care for the uninsured

Abstract: Background For the last 20 years, health provider organizations have made efforts to align mission, values, and everyday practices to ensure high-quality, high-value, and ethical care. However, little attention has been paid to the organizational values and practices of community-based programs that organize and facilitate access to care for uninsured populations. This study aimed to identify and describe organizational values relevant to resource allocation and policy decisions that affect the services offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The similar pattern of wrongful conduct in these upsetting experiences across hospitals and surgeries leads us to contend that the existing practice of unintentionally nullifying IC does not stem solely from lack of communication skills or patronization. Similar to Harrison and Taylor [80], we contend that findings may reflect organizational values in the hospital that the management supports in order to facilitate shorter waiting times and increase the number of surgeries. Managements and surgeons may view the IC process as consuming valuable time and irrelevant for patient decision-making in life-saving surgeries [3].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The similar pattern of wrongful conduct in these upsetting experiences across hospitals and surgeries leads us to contend that the existing practice of unintentionally nullifying IC does not stem solely from lack of communication skills or patronization. Similar to Harrison and Taylor [80], we contend that findings may reflect organizational values in the hospital that the management supports in order to facilitate shorter waiting times and increase the number of surgeries. Managements and surgeons may view the IC process as consuming valuable time and irrelevant for patient decision-making in life-saving surgeries [3].…”
Section: Discussionsupporting
confidence: 77%
“…Changes must take place at both the organizational and team levels. Firstly, organizational and professional values regarding surgical IC may be mapped and clarified as they were mapped for community health organizations [80]. Second, organizational quality measures should ideally include the assessment of proper IC disclosure as experienced and reported by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, Menar and colleagues 58 observe learning health system values include adaptability, equity, inclusiveness, open innovation, scientific integrity, shared accountability, solidarity, and transparency. Harrison and Taylor's 59 earlier work similarly observed stewardship, care quality and access, organizational excellence, decency, and fairness among other values care‐providing organizations espouse. These altruistic values align well with the general orders described here.…”
Section: Discussionmentioning
confidence: 82%
“…The qualitative research methodology contrasting two diverse cases has previously been reported; methods are summarized noting details relevant to the findings reported here (Harrison and Taylor, 2016). The study used a case study approach and multiple data types to triangulate and gain a detailed understanding of the context and process of CAP resource allocation decisions (Creswell, 2006, p. 73; Yin, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Tracing the relationship and factors affecting it could provide a baseline against which future projects can compare the influence of values and contextual, procedural, political, and economic factors in other healthcare organizations, such as insurance benefit package and health system design. As previously described, nine organizational values common to the two participating CAPs were identified as relevant to organizational decision making: stewardship, care quality, access, service to others, community well-being, member independence, organizational excellence, decency, and fairness (Table I) (Harrison and Taylor, 2016). This manuscript describes resource allocation and policy decisions relevant to providing health services to low-income and uninsured individuals and describes the relationship between organizational values and decisions.…”
Section: Introductionmentioning
confidence: 99%